An Update on the Lived Experience of Dry Mouth in Sjögren's Syndrome Patients - Ngo, Di Ying Joanna; Thomson, William Murray (Frontiers in Oral Health, 2021)
This paper aims to provide an update on research findings on the lived experience of dry mouth in Sjögren's Syndrome (SS) patients. Dry mouth is a significant condition that impacts on the daily lives of people with SS. There will first be a summary of the definition, etiology, and manifestation of dry mouth in SS patients. There will next be an overview of the measurement of the impact of dry mouth on the quality of life in SS patients. This will include a deliberation of both quantitative and qualitative methods. Lastly, there will be discussion on the consequences of dry mouth, with a focus on qualitative studies that seek to understand patients' physical, emotional, and social domains of life.